The awareness, efficacy, safety, and time in therapeutic range of warfarin in the Turkish population: WARFARIN-TR - Celik, Ahmet; Izci, Servet; Kobat, Mehmet Ali; Ates, Ahmet Hakan; Cakmak, Abdulkadir; Cakilli, Yasin; Zoghi, Mehdi (Kare Publ, 2016)
Objective: The awareness, time in therapeutic range (TTR), and safety of warfarin therapy were investigated in the adult Turkish population. Methods: This multicenter prospective study includes 4987 patients using warfarin and involved regular international normalized ratio (INR) monitoring between January 1, 2014 and December 31, 2014. TTR was calculated according to F.R. Roosendaal's algorithm. Awareness was evaluated based on the patients' knowledge of warfarin's affect and food-drug interactions. esults: The mean TTR of patients was 49.52 +/- 22.93%. The patients with hypertension (55.3%), coronary artery disease (23.2%), congestive heart failure (24.5%), or smoking habit (20.8%) had significantly lower TTR levels than the others. Of the total number of patients, 42.6% had a mechanical valve, 38.4% had non-valvular atrial fibrillation (AF), and 19% had other indications for warfarin. Patients with other indications had lower TTR levels than those with mechanical valve and non-valvular AF (p=0.018). Warfarin awareness decreased in higher age groups. The knowledge of warfarin's food-drug interactions was 55%. People with higher warfarin awareness had higher TTR levels. Patients with <= 8 INR monitoring/year had lower TTR levels (46.4 +/- 25.3 vs. 51.1 +/- 21.3, respectively, p<0.001) and lower awareness (44.6% vs. 60.6%, p<0.001) than patients with >= 8 INR monitoring/year. In this study, 20.1% of the patients had a bleeding event (major bleeding 15.8%, minor bleeding 84.2%) within a year. Conclusion: Both the mean TTR ratios and awareness of the Turkish population on warfarin therapy were found to be low. It was thought that low TTR levels of the Turkish population may be caused by the low awareness of warfarin, warfarin's food-drug interactions, and high rates of concomitant diseases.
Keywords: time in therapeutic range; warfarin; Turkish population